As contradições que envolvem o trabalho docente no contexto das políticas neoliberais no Brasil: a precarização e os desafios impostos aos docentes - Silva, Valdísia Vieira dos Santos (2024)
The research addresses the process of precarization of teaching work, especially in the neoliberal context that has been consolidating in Brazil since the 1990s. The general objective of the research is to understand the processes of estrangement and precariousness that permeate educational daily life, related to the overwork performed by teachers in their professional practice. The central problematization revolves around the contradictions that emerge from the relationship between neoliberal educational policies and the working conditions of teachers, leading to reflection on how these policies contribute to the precarization of teaching work. The research problem focuses on investigating how the precarization of teaching work occurs and what its implications are for the human condition of students and educators. The justification for conducting this study lies in the need to understand the structural transformations affecting teaching work in a scenario where social guarantees are being progressively reduced. The adopted methodology is of a bibliographical and documentary nature, grounded in historical-dialectical materialism, with a qualitative approach that seeks to identify the working conditions of teachers and the causes of this precarization context. The research conclusions indicate that the precarization of teaching work is a visible trend both in Brazil and globally, affecting public and private educational institutions. The transformations in the labor market, driven by neoliberal policies, have repercussions not only in the education sector but also in various areas, such as industrial production and the cultural field, highlighting the urgent need for public policies that promote better working conditions for teachers.